Integrating SMEs into Global Value Chains : Challenges and Policy Actions in Asia (Book collections on Project MUSE., 2015)
Globalized production networks, or global value chains, provide an opportunity for SMEs to upscale their business models and to grow across borders. This process can enhance SME competitiveness, create more jobs, and promote inclusive growth in developing Asia. The Asian Development Bank (ADB) and the ADB Institute (ADBI) recognize the importance of integrating SMEs into global value chains. To provide pathways for such integration, this study examines ways of encouraging participation in value chains, and explores policy solutions to address the financial and nonfinancial barriers faced by these enterprises.